Pelatihan Social Media Marketing dan Customer Brand Engagement pada UMKM PPMT (Perhimpunan Pelaku Usaha Mikro Tangerang Selatan) - Sudarman, Daman; Hananto, Djoko (Transpublika Publisher, 2024)
The community service aims to provide digital marketing training to MSME entrepreneurs in South Tangerang so that they can utilize social media more effectively. The training seeks to introduce marketing techniques using platforms such as Instagram, Facebook, and TikTok, as well as building brand engagement with customers. In this program, the techniques applied included supervising, interviewing, and providing tutorial-based training and visualization to enhance participants' knowledge on how to create engaging materials and online promotion strategies. The data collected showed a significant improvement in participants' understanding, as seen in the results of the pre-test and post-test, with an average increase in score of 30 points per region. In addition, the training successfully increased social media engagement by 40% and online transactions between 20%-30%, proving the effectiveness of using social media in expanding the market reach of MSMEs. Nevertheless, challenges such as limited infrastructure and internet access remains an obstacle that needs to be overcome to ensure the sustainability of this program.